An exploratory study of discrimination toward contract and private faculty teaching in engineering colleges of the border area of Gurdaspur, India. (16th July 2020) - Mahajan, Vishal; Kumar, Darshan
The tradition and practice of hiring contract labour have been common in many parts of India for the long time back. Although believed to be a monetary necessity, but it has been condemned on the ground that it creates employee exploitation. Though system cannot be abolished exploitation absolutely. In spite, the many harm linked to it, but the structure offers much essential employment to a considerable number of employees. This paper aimed to explore the feelings of contractual faculty towards administrative discrimination in engineering institutions in the border area of Gurdaspur district. In this article helps in finding the relationship between parameters like stress level of work, welfare services, pay satisfaction, provident fund facility, gratuity facility, professional with the satisfaction level of the contract faculty. The diagnosis of this study is that the technical institutions and private university in border area Gurdaspur need to understand the importance of feelings of contract faculty.